PERCEPTION OF SOURCES, EFFECTS AND RESOLUTION METHODS OF CONFLICTS IN TOWN UNIONS OF ANAMBRA STATE, NIGERIA. (2014)
Town Unions (TUs) exist for identifying and resolving communal problems among others in Anambra State. Ironically, many of them are conflict infested. Although many studies have been conducted on conflict, none specifically focused on the nature of social conflict facing TUs in Anambra State. This study therefore investigated the sources, effects and resolution methods of TU conflicts in Anambra State. Marxian theory of social conflict and Ted Gurr’s theory of Relative Deprivation were used as theoretical framework. The study adopted a cross- sectional survey design. Nri was selected through simple random sampling method from a list of 5 communities with two TUs in the state where one should exist. Likewise, Isiagu was selected from a list of 12 communities with care-taker committees. Amansea was selected purposively from list of 160 communities with functional TUs as the study locations. A semi-structured questionnaire was used to collect quantitative data from 516 respondents. The sample frame was the list of TU members as held by ward leaders in the towns. Participants were selected as follows (Nri-128; Isiagu-204 and Amansea-184) using simple random sampling method. Whereas 12 in-depth interviews were conducted on members of vigilante (6), victims of TU conflicts (6), 23 key informants interview were conducted on traditional ruler`s representatives (6), ward leaders (15) and government officials (2) to obtain qualitative data for the study. The quantitative data collected were analysed using descriptive statistics, multiple regression, Chi-square test at 0.05 level of significance. Qualitative data were content analysed. Respondent`s age was 45.3±12.8 years and 65.7% of them were males. Leadership struggle was found to be a significant source of TU conflict in Isiagu (85.1%) but was not in Nri (55.4%) and Amansea (73.2%). Qualitative data attributed the struggle to the absence of a serving monarch in the town. This was not a significant source of TU conflict in Nri and Amansea where serving monarchs existed. Again conflict in Isiagu and Nri arose because identity of some indigenes were politicised. Also, in Isiagu (75.6%), Nri (53.3%) and Amansea (35.9%) of respondents saw State Governments` financial assistance as a source of TU conflict. Qualitative data showed most of the money could be misappropriated by community leaders. In Isiagu (81.0%), Nri (39.0%) and Amansea (35.5%) of respondents saw lack of accountability of TU monies as an internal source of TU conflict. The use of mediators (r = 0.3), elders and traditional rulers (r=0.3), were mostly preferred methods of conflict resolution in the three communities. Conversely, the use of TU constitution (r =0.2), invitation of the police (r =0.2) were not preferred. Leadership struggles and financial assistance foster Town Unions conflict more in towns with caretaker committees in Anambra State. Communities without a serving monarch should be encouraged to have one; since the institution enhances Town Union`s peace. Moreover, culturally approved penal sanctions should be used in the discipline of erring Town Union officials.